Increasing helicopter flight safety in maritime operations with a head mounted display - Walko, C.; Schuchardt, B. (My University, 2019)
To increase flight safety and operational availability for helicopters, the potential benefits of helmet mounted displays (HMD) are investigated, with a focus on maritime operations. Helicopters have long downtimes, due to harsh weather conditions or other visual impairments, especially in maritime scenarios. Flying in these poor conditions can drastically reduce flight safety. It is often difficult to recognize the horizon due to sea fog, and the absence of reference objects can complicate the maritime flight. These conditions and especially the downtimes cost money or, at worst, life’s. Therefore, DLR integrated the augmented reality glasses Microsoft HoloLens into DLR’s simulator AVES to use it as HMD for pilots. Subsequently, displays and symbolism were developed and evaluated. To carry out a piloted simulator study, a maritime scenario was created to measure changes in the pilots’ performance with the HMD, like workload or situational awareness. The paper focuses (a) on the integration of the HoloLens into the simulator with its challenges, solutions and findings, (b) on the symbolism and (c) on the piloted simulator study. Both the quality of the HoloLens as HMD and the study results are very positive. The pilots rated high usability, reduced workload, increased situational awareness and increased safety.